Pengungkapan Kinerja Lingkungan Emisi Karbon Pada Perusahaan Farmasi Proper dan Non Proper di Indonesia - Suherman, Ruben; Faqieh Akbar, Muhamnad; Ramadhan, Yanuar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the differences between PROFER and Non-PROFER regarding the disclosure of the carbon emissions environmental performance of pharmaceutical companies listed on the IDX for the 2019-2023 period. The population in this research is pharmaceutical companies listed on the Indonesia Stock Exchange and having PROFER and Non-PROFER ratings in 2019-2023. Sampling was carried out using the Purposive Sampling method. The research results show that there is no market reaction to mergers and acquisitions which is indicated by the value of no difference in the disclosure of environmental performance of carbon emissions produced by PROFER and NON PROFER pharmaceutical companies on the IDX for the 2019-2023 period.